The Effect of Clothing on Thermoregulatory Responses of Human Body in a Hot Environment (Journal of Fiber Bioengineering and Informatics, 2018)
Studying the effect of clothing on thermoregulatory responses of human body is highly complex becauseclothing, resp. a clothing system, as a heat exchange layer between the body and the environments mustensure a balance between heat production and heat dissipation within different environments and duringvarious activities. The problem becomes more complex in the case of protective clothing, which requiresliquid penetration resistance or impermeability of the material, restricting thus the dry heat flux byconduction, convection, and radiation, as convection and conduction transfer of heat caused by sweatevaporation and condensation. This paper deals with the study of the impact of clothing as baselineclothing, made from different functional materials, on thermoregulatory responses of human body inthe limited heat and moisture transfer context. The results of the investigation show that the effect ofbaseline clothing, as an interface layer, worn under impermeable protective clothing, on thermoregulatoryresponses of human body, is limited during wearing in a hot environment.
Keywords: Clothing; Clothing Material; Cooling Effect; Thermoregulatory Response; Heat and Moisture Transfer